Investigation of the electrocatalytic activity of metalophthalocyanine complexes for hydrogen production from water - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
The electrocatalytic proton reduction activity of metallophthalocyanines was investigated by using Nation (Nf) membrane on ITO electrode embedding different metallophithalocyanine derivatives such as cobalt phthalocyanine (CoPc) and palladium phthalocyanine (PdPc) carrying tetra tricarbetoxyethyl groups. Electrocatalytic studies of CoPc indicated that the proton reduction was catalyzed by the CoPc via the electroreduced (CoPc)-Pc-I(-2) or (CoPc)-Pc-I(-1). PdPc modified ITO electrode exhibited only one cathodic wave which can be easily attributed to the proton reduction. Comparison of this wave with the bare electrode indicates that the complex does not work as a catalyst for proton reduction. Analysis of the CVs of CoPc at different pHs indicates that activity of CoPc varies arbitrarily with increasing pH. The most successful activity is at pH 2.2. (c) 2006 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: hydrogen; phthalocyanine; proton reduction; cyclic voltammetry; chronoamperometry; PROTON REDUCTION; ELECTRON-TRANSFER; POLYMER MEMBRANE; ITO ELECTRODES; VISIBLE-LIGHT; SENSITIZATION; PORPHYRINS; EVOLUTION; CATALYSIS; MOVEMENT